2018
DOI: 10.1039/c8ra00234g
|View full text |Cite
|
Sign up to set email alerts
|

Tribocatalytic behaviour of a TiO2 atmospheric plasma spray (APS) coating in the presence of the friction modifier MoDTC: a parametric study

Abstract: Tribocatalytic behaviour of TiO2 APS coatings in presence of MoDTC additive under boundary lubrication conditions – decomposition mechanism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The absence of core sulfur in molecule MoDTC also rules out (at least in the initial stages) the chemical degradation mechanism proposed by Grossiord et al [8] where only sulfur atoms present in the core of the molecule contribute to the MoS2 generation. The necessary involvement of the sulfur atoms in the ligands of MoDTC 1 remains compatible with at least two proposed mechanisms: the formation of a Linkage Isomer -MoDTC [11,12], or the cleavage of carbonsulfur bonds of the ligand [7,16]. Then, MoSx intermediate products seems needed before generating well-organized MoS2 lamellar sheets during friction as it was proposed previously [7,26].…”
Section: Raman)supporting
confidence: 78%
See 1 more Smart Citation
“…The absence of core sulfur in molecule MoDTC also rules out (at least in the initial stages) the chemical degradation mechanism proposed by Grossiord et al [8] where only sulfur atoms present in the core of the molecule contribute to the MoS2 generation. The necessary involvement of the sulfur atoms in the ligands of MoDTC 1 remains compatible with at least two proposed mechanisms: the formation of a Linkage Isomer -MoDTC [11,12], or the cleavage of carbonsulfur bonds of the ligand [7,16]. Then, MoSx intermediate products seems needed before generating well-organized MoS2 lamellar sheets during friction as it was proposed previously [7,26].…”
Section: Raman)supporting
confidence: 78%
“…Even if the mechanism of action of MoDTC has been widely studied, [7][8][9][11][12][13][14][15] [11,12] or by cleavage of carbon-sulfur bonds of the ligand, schematized as (R2NC) [(S2Mo(O)(µ-S)2Mo(O)S2)] (CNR2) [7,16]. All these approaches suggest that core [MonSm] fragments called MoSx intermediate products [7] are needed at some stage in generating well-organized MoS2 lamellar sheets during friction.…”
Section: Introductionmentioning
confidence: 99%
“…Onodera et al [37] reported that MoDTC transformed into a bridging isomer of MoDTC (Li-MoDTC) at moderate temperatures. Deshpande et al [38,39] reported that the decomposition of MoDTC was accelerated by the catalysis of a TiO 2 atmospheric plasma-spray coating.…”
Section: Chemical Structure Of Tribofilmmentioning
confidence: 99%
“…With the oxygen vacancies as the reductive species, these decomposed MoDTC into MoS 2 . 74 Based on this work, the team explored the tribological performance of lubricants containing nano-TiO 2 and MoDTC in steel–steel friction layers. The same reaction mechanism was used, and the generated MoS 2 was the main reason for reducing friction.…”
Section: Applications Of Tribocatalysismentioning
confidence: 99%